Pemberdayaan Kelompok Disabilitas dalam Upaya Meningkatkan Kemandirian Wirausaha melalui Pelatihan Kripik Pisang - Wisnu Setiadi (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2024)
Disability is still a strategic issue that continues to be voiced in the public sphere to get their rights. The difficulty of getting a job and the lack of self-confidence add to the bad stigma of disability for people with disabilities. The purpose of writing this research as a momentum to bring awareness of entrepreneurship for disabled groups. On the other hand, as an increase in the capacity of managing banana skills into chips with flavor variants. This research service uses Participatory Learning Methods with techniques in the form of training simulations ranging from planning, implementation and evaluation. The research method is descriptive-qualitative with observation data collection, interviews, and documentation. The results of the study explained that the training started from the planning stage by looking from an objective point of view at the members of the village Disability Group and looking at the direction of the SIGAB companion at the KDK. Banana chips processing training has an impact on participants, namely adding insight into the selection of bananas, frying techniques, and providing flavor variants. In order for the sustainability of the program to be achieved more optimally to realize the disabled community who are independent entrepreneurs, partners with related stakeholders are needed.